Whole genome sequence of the Treponema pallidum subsp. endemicum strain Bosnia A: the genome is related to yaws treponemes but contains few loci similar to syphilis treponemes. - Barbora Staudová; Michal Strouhal; Marie Zobaníková; Darina Cejková; Lucinda L Fulton; Lei Chen; Lorenzo Giacani; Arturo Centurion-Lara; Sylvia M Bruisten; Erica Sodergren; George M Weinstock; David Smajs (Public Library of Science (PLoS), 2014)
T. pallidum subsp. endemicum (TEN) is the causative agent of bejel (also known as endemic syphilis). Clinical symptoms of syphilis and bejel are overlapping and the epidemiological context is important for correct diagnosis of both diseases. In contrast to syphilis, caused by T. pallidum subsp. pallidum (TPA), TEN infections are usually spread by direct contact or contaminated utensils rather than by sexual contact. Bejel is most often seen in western Africa and in the Middle East. The strain Bosnia A was isolated in 1950 in Bosnia, southern Europe.The complete genome of the Bosnia A strain was amplified and sequenced using the pooled segment genome sequencing (PSGS) method and a combination of three next-generation sequencing techniques (SOLiD, Roche 454, and Illumina). Using this approach, a total combined average genome coverage of 513× was achieved. The size of the Bosnia A genome was found to be 1,137,653 bp, i.e. 1.6-2.8 kbp shorter than any previously published genomes of uncultivable pathogenic treponemes. Conserved gene synteny was found in the Bosnia A genome compared to other sequenced syphilis and yaws treponemes. The TEN Bosnia A genome was distinct but very similar to the genome of yaws-causing T. pallidum subsp. pertenue (TPE) strains. Interestingly, the TEN Bosnia A genome was found to contain several sequences, which so far, have been uniquely identified only in syphilis treponemes.The genome of TEN Bosnia A contains several sequences thought to be unique to TPA strains; these sequences very likely represent remnants of recombination events during the evolution of TEN treponemes. This finding emphasizes a possible role of repeated horizontal gene transfer between treponemal subspecies in shaping the Bosnia A genome.